Thinking about personality: Comment on Hogan and Foster (2016) - Sergei Shchebetenko (International Journal of Personality Psychology, 2017)
Hogan and Foster’s socioanalytic theory has many strengths, in particular in its function as an umbrella approach that takes into account traits, reputations, and other social aspects of personality. Hogan and Foster criticize (self-reported) traits as being elusive neuro-psychicentities, irrelevant for the understanding everyday social life; traittheoryunderestimatesthe importance of reputation. However, reputations and agendas, the central elements of socioanalytic theory, are also kinds of neuro-psychic entities, andreputationappearstobe an evenmoreambiguous phenomenon than a self-reported trait. Moreover, from a measurement perspective, traits are not neuro-psychic entities, nor are they action-psychic entities, but rather interpretations and opinions activated when participants fill out questionnaires. Despite the criticism provided by the socioanalytic theory, self-reported traits remain viable for the prediction of behavioural and life outcomes. In addition, self-reported traits can be diverse in nature and include, along with the abstract traits, meta-traits, evaluations of traits, and other structures which make incremental—as compared to traits themselves—contributions to life outcomes.